FAKTOR YANG MEMPENGARUHI MINAT BELAJAR MATEMATIKA SISWA SD PADA TOPIK GEOMETRI DAN UPAYA PENINGKATANNYA - Putri, Onma Nikita; Chanisah Azzahra; Rizka Fadhila Siregar; Syahrial (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to determine the level of interest in learning mathematics among fourth-grade students at SDN 106161 Laut Dendang on the topic of geometry and to identify the factors that influence it. The study uses a quantitative approach with a descriptive method. The research subjects consisted of 32 students who were given a questionnaire containing 17 questions about their interest in learning mathematics on the subject of flat shapes. The results showed that 50% of students had a high interest in learning, while the other 50% showed a low interest in learning. This indicates that mathematics learning on the topic of geometry is not yet fully interesting for all students. Factors that influence learning interest include students' perceptions of the difficulty of the material, the learning methods used by teachers, the availability of learning media, and support from the surrounding environment. Recommended solutions include the application of interactive learning methods, the use of concrete and digital media, linking the material to everyday life, and increasing collaboration between teachers, students, and parents. This study is expected to provide input for teachers and schools to increase student interest and learning outcomes in mathematics.